The influence of technological additives on the foaming process of rigid polyvinylchloride compositions with azodicarbonamide - A. V. Markov; Tahseen A. Saki (Тонкие химические технологии)
Foaming process of rigid PVC compositions with azodikarbonamid in the presence of different modifying and processing additives was studied. Additives which increase or decrease foaming coefficient of rigid PVC were identified and the reasons of observable phenomenon were examined.